2007
DOI: 10.1177/1066896906295956
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tuberculosis in Adult Polycystic Kidney Disease: Report of 2 Cases and Review of the Literature

Abstract: Adult polycystic kidney disease (APKD) is a common and potentially fatal disease, leading to end-stage renal failure in 50% of cases. The disease is frequently complicated by arterial hypertension, bacterial pyelonephritis, and hematuria. The association between APKD and tuberculosis has rarely been reported and is related to a more unfavorable course since the infection becomes refractory to specific treatment. The authors report 2 cases of renal tuberculosis diagnosed in the native nephrectomy specimens of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
“…Renal TB has also been noted in native adult polycystic kidneys, in immunocompromised transplant recipients[61] in association with renal replacement lipomatosis,[62] and in horse-shoe kidneys.…”
Section: Pathogenesismentioning
confidence: 99%